From small‐scale studies to an encompassing view: Inhibiting inflammation and clinically relevant enzymes with various extracts of Primula vulgaris using in vitro and in silico techniques - Inci Kurt‐Celep; Nilofar; Mehmet Veysi Cetiz; Dimitrina Zheleva‐Dimitrova; Reneta Gevrenova; Engin Celep; Kouadio Ibrahime Sinan; Evren Yildiztugay; Claudio Ferrante; Gokhan Zengin (Food Frontiers)
Abstract The genus Primula holds great importance as a source of traditional remedies in various folk medicine systems. In the present study, we investigated the chemical composition and biological properties of different extracts (ethyl acetate, ethanol, ethanol/water, and water) of aerial parts and rhizomes of Primula vulgaris. To determine the chemical profile, the extracts were analyzed using ultrahigh performance liquid chromatography‐high‐resolution mass spectrometry (UHPLC‐HRMS) technique and flavonoids were a major group in this profile. The antioxidant capacity was demonstrated by in vitro chemical tests and in general the ethanol/water extract was found to be the most potent. Enzyme inhibition was studied against various enzymes and ethanol and ethanol/water extracts were more active than others. To assess the anti‐inflammatory potential of the extracts at the molecular level, human dermal fibroblasts (HDF) were treated with lipopolysaccharide (LPS). In vitro experiments showed that the levels of nuclear factor kappa B (NFKB), receptor for advanced glycation endproducts (RAGE), activator protein‐1 (AP‐1), interleukin 6 (IL‐6), interleukin 17 (IL‐17) and tumor necrosis factor (TNF)‐alpha were significantly reduced after treatment with the tested extracts. In addition, the extracts showed an inhibitory effect on the enzymes collagenase, elastase, and hyaluronidase, which are involved in the inflammatory process and destabilization of the extracellular matrix (ECM). P. vulgaris has been observed to modulate matrix metalloproteinase (MMP) synthesis by decreasing the concentration of cellular reactive oxygen species (ROS) during LPS‐induced inflammation. This study also examined the molecular binding and dynamic behavior of various enzymes and proteins associated with skin and infections using ligands derived from the tested extracts. Simulations with AutoDock Vina V1.1.2 and GROMACS 2023.1 showed that isoquercetin in particular showed superior performance in interactions with hyaluronidase. These findings are important for the development of potential therapeutic strategies for skin health and infection control. In summary, P. vulgaris can be considered as an important source of natural bioactive compounds for the development of effective health‐promoting applications in nutraceuticals, pharmaceuticals, and cosmetics